The sign of the beaver - Speare, Elizabeth George (Boston : Houghton Mifflin, 1983)
Left alone to guard the family's wilderness home in eighteenth-century Maine, a boy is hard-pressed to survive until local Indians teach him their skills.
Keywords: Frontier and pioneer life -- Fiction; Indians of North America -- Fiction; Survival -- Fiction; Friendship -- Fiction; Maine -- History -- 1775-1865 -- Fiction